Lithium manganese iron phosphate material as well as preparation method and application thereof
Through specific preparation methods, the gap in compaction performance and circulation performance of lithium manganese iron phosphate material is solved, and its comprehensive performance in the battery field is improved.
Patent Information
- Application Number
- CN202411580550.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
There is a gap in compaction performance and circulation performance of lithium manganese iron phosphate materials, which affects its development in the battery field.
Through specific preparation methods, including mixing iron, manganese, phosphorus, fluorine source with water, adjusting pH and heating reaction, performing solid-liquid separation, sintering and crushing, and then mixing with lithium, carbon source and additives, Multiple grinding, drying and sintering finally result in a high-performance lithium manganese phosphate material.
The compaction performance, circulation performance and comprehensive performance of lithium manganese iron phosphate material are improved, making it more stable and efficient in battery applications.
Smart Images

Figure BDA0005123454670000181 
Figure BDA0005123454670000191
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium manganese iron phosphate material and a preparation method and application thereof. Background Art
[0002] Lithium iron phosphate is a material widely used in the positive electrode of power batteries. It has the advantages of long cycle life and good safety, and is favored by the electric vehicle market. However, the working voltage of lithium iron phosphate is low. 3+ / Fe 2+ Relative to Li + The potential of / Li is only 3.4V, which makes the specific energy of lithium iron phosphate material low, which limits its development to a certain extent. Lithium manganese phosphate material has a similar structure to lithium iron phosphate material, although its working voltage is higher. 3+ / Fe 2+ The potential relative to Li+ / Li is 4.1V, which makes the specific energy of lithium manganese phosphate material higher, but the conductivity of lithium manganese phosphate material is extremely poor, which in turn limits the development and application of lithium manganese phosphate material.
[0003] Lithium iron manganese phosphate material combines the advantages of the above two materials and makes up for the shortcomings of the above two materials. It has both 4V capacity and good conductivity. Based on the advantages of lithium iron manganese phosphate material such as high specific energy performance and good conductivity, lithium iron manganese phosphate material is becoming a potential application material for the new generation of power batteries.
[0004] At present, the challenges faced by lithium iron manganese phosphate materials are mainly that the compaction performance and cycle performance are still far behind those of lithium iron phosphate materials. Therefore, improving the compaction performance of lithium iron manganese phosphate materials and the capacitance performance and cycle stability performance when used in batteries, and improving their comprehensive performance, are of great significance for promoting the further development and application of lithium iron manganese phosphate materials in the battery field. Summary of the invention
[0005] The main purpose of the present invention is to provide a high-performance lithium iron manganese phosphate material and its preparation method and application, so as to improve the problems of poor compaction performance of the lithium iron manganese phosphate material in the prior art and poor capacitance performance and cycle performance when used in batteries, thereby further improving the comprehensive performance of the lithium iron manganese phosphate material.
[0006] In order to solve the above problems, the present invention provides a method for preparing a lithium iron manganese phosphate material, which comprises the following steps: step (1), mixing an iron source, a manganese source, a phosphorus source, a fluorine source and water, and then adjusting the pH with sulfuric acid to obtain a mixed solution A; step (2), heating the mixed solution A for reaction; performing solid-liquid separation, sintering and crushing on the mixed slurry obtained by the reaction to obtain a ferromanganese phosphate precursor; step (3), mixing the ferromanganese phosphate precursor, a lithium source, a first carbon source, an additive and water, and then sequentially performing wet grinding, first spray drying, first sintering and dry grinding to obtain a lithium iron manganese phosphate premix; step (4), mixing the lithium iron manganese phosphate premix, a second carbon source and water, and then sequentially performing a second spray drying, a second sintering and crushing to obtain a lithium iron manganese phosphate material.
[0007] Furthermore, in step (1), the molar ratio of Fe:Mn:P:F in the iron source, manganese source, phosphorus source and fluorine source is X:(1-X):1:Y, wherein X is 0.3 to 0.5 and Y is 0.001 to 0.005.
[0008] Furthermore, in step (3), the molar ratio of P:Li:M in the ferromanganese phosphate precursor, the lithium source and the additive is 1:(1-1.03):(0.0008-0.0012), wherein M is the metal element in the additive.
[0009] Furthermore, the first carbon source is one or more of glucose, sucrose and citric acid; the second carbon source is one or more of polyethylene glycol, polyvinyl alcohol and polyacrylonitrile; preferably, the additive is one or more of magnesium oxide, titanium dioxide, aluminum oxide, niobium pentoxide and yttrium oxide.
[0010] Furthermore, in step (1), sulfuric acid is used to adjust the pH to 2-2.5, and the solid content in the mixed solution A is preferably 10-25%; preferably, the iron source is one or more of ferrous oxide, ferric oxide, ferric oxide and ferric sulfate; preferably, the manganese source is one or more of manganese oxide, manganese tetraoxide and manganese sulfate; preferably, the phosphorus source is phosphoric acid and / or ammonium dihydrogen phosphate; preferably, the fluorine source is lithium fluoride and / or hydrofluoric acid; preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide and lithium oxide.
[0011] Furthermore, the heating reaction time in step (2) is 3 to 5 hours, the temperature is 80 to 100°C, and the stirring speed is 50 to 70 rpm; preferably, during the solid-liquid separation operation in step (2), the mixed slurry is centrifuged, filtered, washed with water, and dried; further preferably, the centrifugal speed is 1500 to 1800 rpm, the number of washings is 4 to 7 times, the drying temperature is 70 to 90°C, and the time is 4 to 6 hours; preferably, the sintering process in step (2) is heated to 500 to 650°C at a heating rate of 3 to 5°C / min, and the sintering is kept warm for 3 to 4 hours; preferably, the particle size of the ferromanganese phosphate precursor obtained after crushing in step (2) is 3μm≤D50≤6μm, D100≤70μm; preferably, the first sintering and the second sintering are carried out under nitrogen or inert gas atmosphere, and preferably the inert gas is argon.
[0012] Furthermore, the solid content of the slurry after mixing in step (3) is 40-50%; preferably, the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.55μm, D100≤2μm; preferably, the inlet temperature of the first spray drying is 260-280°C, and the exhaust temperature is 100-110°C; preferably, the first sintering process is first heated to 150-250°C at a heating rate of 3-5°C / min, sintered at this temperature for 1-2h, and then heated to 450-550°C, and sintered at this temperature for 3-4h; preferably, the particle size of the lithium manganese iron phosphate premix obtained after dry grinding is 0.5μm≤D50≤0.7μm, D100≤5μm; preferably, the carbon content of the lithium manganese iron phosphate premix is 0.2-0.4%.
[0013] Furthermore, the solid content of the slurry after mixing in step (4) is 40-50%; preferably, the inlet air temperature of the second spray drying is 260-280°C, and the exhaust air temperature is 100-110°C; preferably, the second sintering process is first heated to 350-450°C at a heating rate of 3-5°C / min, and sintered at this temperature for 1-2 hours, and then heated to 700-780°C, and sintered at this temperature for 8-10 hours; preferably, the particle size of the lithium manganese iron phosphate material obtained after crushing is 0.8μm≤D50≤1.2μm, D100≤10μm; preferably, the carbon content of the lithium manganese iron phosphate material is 1.3-1.5%.
[0014] According to another aspect of the present invention, a lithium iron manganese phosphate material is further provided. The lithium iron manganese phosphate material is prepared by the above-mentioned method for preparing the lithium iron manganese phosphate material, and comprises Li (1~1.03) Fe X Mn (1-X) M (0.0008~0.0012) PO (4-Y) F Yand carbon compounded therein, wherein X is 0.3-0.5, Y is 0.001-0.005, the carbon content is 1.3-1.5%, and M is one or more metal elements selected from magnesium oxide, titanium dioxide, aluminum oxide, niobium pentoxide and yttrium oxide.
[0015] According to the third aspect of the present invention, a battery positive electrode plate is also provided, which contains the above-mentioned lithium iron manganese phosphate material, and the preparation method of the battery positive electrode plate comprises the following steps: S1: mixing the lithium iron manganese phosphate material with a conductive agent and a binder to obtain a lithium iron manganese phosphate slurry; S2: coating the lithium iron manganese phosphate slurry on a carbon-coated aluminum foil current collector, and then forming a battery positive electrode through rolling, assembly, and injection processes; preferably, the lithium iron manganese phosphate slurry has a solid content of 30-40%; preferably, the conductive agent is conductive carbon black, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone; preferably, the injection contains a lithium iron manganese phosphate electrolyte and a complex, and the mass ratio of the lithium iron manganese phosphate electrolyte to the complex in the injection is 1000:(1-2); preferably, the complex is ethylenediaminetetraacetic acid and / or sulfosalicylic acid; preferably, the coating thickness is 150-200 μm.
[0016] The present invention provides a method for preparing a lithium iron manganese phosphate material. The method first adds a fluorine source to a ferromanganese phosphate precursor, and then adds a lithium source and other substances to the prepared ferromanganese phosphate precursor, so that the obtained lithium iron manganese phosphate material can fully exert the transmission current function of lithium in the material on the basis of inheriting the performance of the ferromanganese phosphate precursor material. In addition, through the double-step composite carbon source and multiple grinding and sintering of the intermediate mixture in the preparation process, the compaction performance and cycle performance of the lithium iron manganese phosphate material are further improved, and the comprehensive performance of the lithium iron manganese phosphate material is improved. In addition, the preparation method has a simple process and is easy to operate. The obtained composite material has stable performance and high repeatability. It will be made into a battery positive electrode plate and applied to a battery, and the comprehensive performance of the obtained battery can be further improved. DETAILED DESCRIPTION
[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0018] As mentioned in the background technology section, lithium manganese iron phosphate material has both high specific energy performance and good conductivity, and is a very promising power battery material. However, lithium manganese iron phosphate material still has problems such as insufficient compaction performance and cycle performance, and poor overall performance, which seriously affects the further development of lithium manganese iron phosphate material in the battery field.
[0019] In order to solve the above problems, the present invention provides a method for preparing a lithium iron manganese phosphate material, which comprises the following steps: step (1), mixing an iron source, a manganese source, a phosphorus source, a fluorine source and water, and then adjusting the pH with sulfuric acid to obtain a mixed solution A; step (2), heating the mixed solution A for reaction; performing solid-liquid separation, sintering and crushing on the mixed slurry obtained by the reaction to obtain a ferromanganese phosphate precursor; step (3), mixing the ferromanganese phosphate precursor, a lithium source, a first carbon source, an additive and water, and then sequentially performing wet grinding, first spray drying, first sintering and dry grinding to obtain a lithium iron manganese phosphate premix; step (4), mixing the lithium iron manganese phosphate premix, a second carbon source and water, and then sequentially performing a second spray drying, a second sintering and crushing to obtain a lithium iron manganese phosphate material.
[0020] Specifically, the method first fully mixes the iron source, manganese source, phosphorus source, fluorine source and water, adjusts the pH of the mixed solution with sulfuric acid, and then fully reacts the components in the mixed solution A by heating, and obtains the ferromanganese phosphate precursor by performing solid-liquid separation, solid-phase sintering, crushing and other operations on the reaction slurry. Then, the lithium source, the first carbon source, the additive and the ferromanganese phosphate precursor are further mixed, and wet grinding, spray drying, sintering, dry grinding and other operations are performed in sequence to achieve the purpose of doping the lithium source and coating the first carbon source on the ferromanganese phosphate precursor material. Finally, by mixing with the second carbon source, and repeating the spray drying, sintering and crushing operations, the carbon source is further coated, so that the obtained lithium iron manganese phosphate material is more uniform and the performance is more stable.
[0021] In particular, the present application also dopes fluorine in the process of preparing the lithium iron manganese phosphate material. The doped fluorine element can interact with the metal elements in the material, thereby improving the comprehensive performance of the lithium iron manganese phosphate material. In particular, the operation of doping fluorine in the lithium iron manganese phosphate material in the present application is different from the conventional operation. The conventional method for preparing fluorine-doped lithium iron manganese phosphate material generally directly mixes and reacts materials such as iron source, manganese source, phosphorus source, fluorine source and lithium source, and then performs a series of other operations such as carbon coating. The preparation method described in the present application is to first mix the iron source, manganese source, phosphorus source and fluorine source, and then obtain a manganese iron phosphate precursor through a series of operations such as reaction, separation, sintering and crushing; then mix the lithium source, the first carbon source and the additive with the manganese iron phosphate precursor to obtain a manganese iron phosphate premix, and then perform further operations to prepare the lithium iron manganese phosphate material. First, the fluorine source is first mixed with the iron source, manganese source, and phosphorus source to form a ferromanganese phosphate precursor material, and then compounded with a lithium source, so that the prepared lithium iron manganese phosphate material can further exert the characteristics of the electronic conductivity and ionic conductivity of lithium in the material on the basis of inheriting the many excellent properties of the ferromanganese phosphate material, and the performance of the two parts of the material can be further superimposed and improved. Second, if the iron source, manganese source, phosphorus source, fluorine source, and lithium source are mixed together to react to prepare the lithium iron manganese phosphate material according to the conventional method, the lithium fluoride formed by the fluorine element and the lithium element is unstable under the action of water, thereby affecting the various components in the lithium iron manganese phosphate material. The preparation method described in the present invention can effectively improve this problem. The preparation method described in this application can produce a beneficial effect on improving the comprehensive performance of the lithium iron manganese phosphate material.
[0022] In addition, the present application also performs two carbon source doping and coating operations and repeated grinding, repeated sintering, drying and crushing in the process of preparing lithium manganese iron phosphate materials, which can make the various components of the obtained lithium manganese iron phosphate materials more uniformly mixed, and the various properties of the obtained materials will be more stable, and the compaction performance and cycle performance will be better when applied to batteries. The doping of additives can also effectively benefit the performance of lithium manganese iron phosphate materials.
[0023] In summary, the lithium iron manganese phosphate material preparation method provided by the present application has good stability and uniformity, and can effectively improve the comprehensive properties of the lithium iron manganese phosphate material, such as compaction performance and conductivity, and further improve the capacitance and cycle stability of the lithium iron manganese phosphate material when used in batteries. In addition, the method also has the advantages of high repeatability and simple operation.
[0024] In order to better improve the performance of lithium iron manganese phosphate material, in a preferred embodiment, the molar ratio of Fe:Mn:P:F in the iron source, manganese source, phosphorus source and fluorine source in step (1) is X:(1-X):1:Y, wherein X is 0.3-0.5 and Y is 0.001-0.005. The ratio of each component in the material will have a great influence on the performance of lithium iron manganese phosphate material. When preparing the iron manganese phosphate precursor, controlling each component of Fe, Mn, P and F in the above components within the above range is beneficial to improving the conductivity and cycle performance of the lithium iron manganese phosphate material.
[0025] In a preferred embodiment, in the process of preparing the lithium iron manganese phosphate material, the molar ratio of P:Li:M in the iron manganese phosphate precursor, the lithium source and the additive in step (3) is 1:(1-1.03):(0.0008-0.0012), wherein M is the metal element in the additive. By controlling the addition amount of lithium and the addition amount of the additive within the above range, the comprehensive performance of the lithium iron manganese phosphate material can be further improved.
[0026] In a preferred embodiment, the first carbon source is one or more of glucose, sucrose, and citric acid; the second carbon source is one or more of polyethylene glycol, polyvinyl alcohol, and polyacrylonitrile. In the process of preparing the lithium iron manganese phosphate material, two carbon source doping and coating operations were carried out respectively. The carbon source for the first doping and coating was one or more of glucose, sucrose, and citric acid. The doping of the carbon source this time can reduce the material on the one hand, and on the other hand, it can make carbon coated on the surface of the lithium iron manganese phosphate material, improving the material's electrical conductivity, cycle performance, and compaction performance. The second doping and coating carbon source is one or more of polyethylene glycol, polyvinyl alcohol, and polyacrylonitrile. This operation can further coat the obtained carbon-containing material, make the obtained composite material carbon coating more uniform, and the comprehensive performance in all aspects will be better. It can also play a role in limiting particle growth. In addition, the first carbon source and the second carbon source are selected as the above-mentioned specific types, mainly because the glucose, sucrose and citric acid in the first carbon source have good reducing properties, and can be used in smaller amounts, and also have the advantage of good economy, especially in large-scale production processes, which can better save costs; and the polyethylene glycol, polyvinyl alcohol and polyacrylonitrile in the second carbon source have a good effect of limiting particle growth, and can better control the particle number and size of the lithium manganese iron phosphate material during the preparation process.
[0027] In a preferred embodiment, the additive is one or more of magnesium oxide, titanium dioxide, aluminum oxide, niobium pentoxide and yttrium oxide. One or more of these high-valent metal oxides are doped as additives in the lithium iron manganese phosphate material, which can inhibit the further growth of the crystal plane of the lithium iron manganese phosphate material during the growth process, thereby effectively controlling the particle size of the lithium iron manganese phosphate material. Secondly, doping the lithium iron manganese phosphate material with high-valent metal oxides can also form crystal nucleus defects with the metal elements in the high-valent metal oxides and the metal elements manganese, iron, etc. in the lithium iron manganese phosphate material, further improving the comprehensive properties of the material such as the cycle performance and electrical conductivity.
[0028] In a preferred embodiment, sulfuric acid is used to adjust the pH to 2-2.5 in step (1), and sulfuric acid is used to adjust the pH to 2-2.5 after mixing the iron source, manganese source, phosphorus source, and fluorine source with water. Placing the system in an acidic environment can make the components react better, which is conducive to the generation of ferromanganese phosphate precursor. Preferably, the solid content in the mixed solution A is 10-25%. The ferromanganese phosphate precursor obtained by controlling the solid content in the mixed solution A within this range is more evenly mixed and reacts better, which is conducive to the subsequent preparation of lithium iron manganese phosphate material. Preferably, the iron source is one or more of ferrous oxide, ferrous oxide and ferric sulfate; preferably, the manganese source is one or more of manganese oxide, manganese tetraoxide and manganese sulfate; preferably, the phosphorus source is phosphoric acid and / or ammonium dihydrogen phosphate; preferably, the fluorine source is lithium fluoride and / or hydrofluoric acid; preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide and lithium oxide. The above raw materials are selected in the process of preparing lithium iron manganese phosphate material, so that the obtained lithium iron manganese phosphate material has better comprehensive performance.
[0029] In a preferred embodiment, the heating reaction time in step (2) is 3 to 5 hours, the temperature is 80 to 100°C, and the stirring speed is 50 to 70 rpm. Under this condition, each component can react more fully. Preferably, during the solid-liquid separation operation in step (2), the mixed slurry is centrifuged, filtered, washed with water, and dried; further preferably, the centrifugal speed is 1500 to 1800 rpm, the number of washings is 4 to 7 times, the drying temperature is 70 to 90°C, and the time is 4 to 6 hours. The operation of solid-liquid separation of the mixed slurry is more conducive to the subsequent sintering to prepare the ferromanganese phosphate precursor. Preferably, the sintering process in step (2) is heated to 500-650°C at a heating rate of 3-5°C / min, and the temperature is kept for 3-4 hours; preferably, the particle size of the ferromanganese phosphate precursor obtained after crushing in step (2) is 3μ≤D50≤6μm, D100≤70μm; preferably, the first sintering and the second sintering are carried out under nitrogen or inert gas atmosphere, preferably the inert gas is argon. In the process of preparing lithium manganese iron phosphate material, the sintering temperature and time are crucial to the structure and properties of the material. Controlling the sintering temperature and time within the above range, as well as controlling the particle size of the ferromanganese phosphate precursor after crushing within the above range, can produce a beneficial effect on improving the comprehensive performance of the preparation of lithium manganese iron phosphate material.
[0030] In step (3), the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water are mixed, and wet grinding, first spray drying, first sintering and dry grinding are carried out in sequence to obtain a manganese iron phosphate lithium premix. In a preferred embodiment, the solid content of the slurry after mixing in step (3) is 40-50%. Controlling the overall solid content of the ferromanganese phosphate precursor, the lithium source, the first carbon source and the additive within the above range and controlling their proportions can make the manganese iron phosphate lithium material have better comprehensive properties. Preferably, the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.55μm, D100≤2μm; preferably, the air inlet temperature of the first spray drying is 260-280℃, and the exhaust temperature is 100-110℃; preferably, the first sintering process is first heated to 150-250℃ at a heating rate of 3-5℃ / min, sintered at a temperature of 1-2h, and then heated to 450-550℃, sintered at a temperature of 3-4h; preferably, the particle size of the lithium manganese iron phosphate premix obtained after dry grinding is 0.5μm≤D50≤0.7μm, D100≤5μm; preferably, the carbon content of the lithium manganese iron phosphate premix is 0.2-0.4%. All of the above conditions can make the lithium manganese iron phosphate material have better comprehensive properties such as compaction performance, cycle performance and conductivity. Preferably, the stirring speed during mixing is controlled to be 70-100 rpm so that the components can be mixed more evenly.
[0031] In a preferred embodiment, the solid content of the slurry after mixing in step (4) is 40-50%; preferably, the air inlet temperature of the second spray drying is 260-280°C, and the exhaust temperature is 100-110°C; preferably, the second sintering process is first heated to 350-450°C at a heating rate of 3-5°C / min, sintered at this temperature for 1-2 hours, and then heated to 700-780°C, sintered at this temperature for 8-10 hours; preferably, the particle size of the lithium manganese iron phosphate material obtained after crushing is 0.8μm≤D50≤1.2μm, D100≤10μm; preferably, the carbon content of the lithium manganese iron phosphate material is 1.3-1.5%. In step (5), the secondary carbon doping and coating process is carried out, and the operating conditions of each step are controlled within the above range, which can further improve the comprehensive performance of the lithium manganese iron phosphate material. Preferably, the stirring speed during mixing is controlled to be 70-100rpm, at which time the components are mixed more evenly.
[0032] According to another aspect of the present invention, a lithium iron manganese phosphate material is further provided. The lithium iron manganese phosphate material is prepared by the above-mentioned method for preparing the lithium iron manganese phosphate material, and comprises Li (1~1.03) Fe X Mn (1-X) M (0.0008~0.0012) PO (4-Y) F Y and carbon compounded therein, wherein X is 0.3-0.5, Y is 0.001-0.005, the carbon content is 1.3-1.5%, and M is one or more metal elements selected from magnesium oxide, titanium dioxide, aluminum oxide, niobium pentoxide and yttrium oxide. The lithium manganese iron phosphate material has better compaction performance and cycle stability.
[0033] According to the third aspect of the present invention, a battery positive electrode sheet is also provided, the battery positive electrode comprises the above-mentioned lithium iron manganese phosphate material, and the preparation method of the battery positive electrode sheet comprises the following steps: S1: mixing the lithium iron manganese phosphate material with a conductive agent, a binder, and a solvent to obtain a lithium iron manganese phosphate slurry; S2: coating the lithium iron manganese phosphate slurry on a carbon-coated aluminum foil current collector, and then rolling, assembling, and injecting to form a battery positive electrode. Preferably, the solid content of the lithium iron manganese phosphate slurry is 30-40%; preferably, the conductive agent is conductive carbon black, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone; preferably, the injection contains a lithium iron manganese phosphate electrolyte and a complex, and the mass ratio of the lithium iron manganese phosphate electrolyte and the complex in the injection is 1000: (1-2); preferably, the complex is ethylenediaminetetraacetic acid and / or sulfosalicylic acid; preferably, the coating thickness is 150-200 μm. In the process of preparing the battery positive electrode, controlling the operation within the above range can make the obtained battery positive electrode have better performance. Preferably, the weight ratio of lithium manganese iron phosphate material to the conductive agent and the binder is 0.95:0.03:0.02.
[0034] In particular, in the process of preparing the positive electrode of the battery using the prepared lithium iron manganese phosphate material, the injection liquid contains lithium iron manganese phosphate electrolyte and complex, and the mass ratio of lithium iron manganese phosphate electrolyte and complex in the injection liquid is controlled to be 1000: (1-2). Adding a small amount of complexing agent to the injection liquid can effectively fix the manganese ions in the lithium iron manganese phosphate material, thereby effectively inhibiting the dissolution of manganese ions in the material due to the Janh-Teller effect, thereby further improving the cycle performance of the battery.
[0035] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0036] It is necessary to explain the sources of some materials in the examples here: conductive carbon black (AC80), polyvinylidene fluoride (Arkema SHV-900), potassium chloride (negative electrode material, produced by Zhongke Xingcheng).
[0037] Example 1
[0038] (1) Preparation of lithium manganese iron phosphate materials
[0039] The iron source is ferroferric oxide, the manganese source is manganese tetraoxide, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the molar ratio of Fe:Mn:P:F is 0.3:0.7:1:0.001; the lithium source is lithium carbonate, the first carbon source is glucose, and the additive is magnesium oxide, and the molar ratio of P:Li:Mg in the manganese iron phosphate precursor is 1:1:0.001; the second carbon source is polyethylene glycol (PEG).
[0040] The iron source, manganese source, phosphorus source, fluorine source and water were mixed at a solid content of 10%, the pH was adjusted to 2 with sulfuric acid, and the mixture was mixed evenly at a speed of 300rmb to obtain a mixed solution A; the mixed solution A was placed in a hydrothermal reactor, reacted at a temperature of 80°C and a stirring speed of 50rpm for 3h, and then centrifuged, filtered, washed and dried with a centrifuge at a speed of 1500rpm, washed with water 4 times, and dried at 70°C for 6h to obtain a solid phase material B; the solid phase material B was placed in a muffle furnace and heated to 5 at a heating rate of 3°C / min; 00℃ and sintering for 3h, then crushing to obtain ferromanganese phosphate precursor, the particle size of the ferromanganese phosphate precursor after crushing is 3μm≤D50≤4μm, D100≤50μm; mixing the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water at a solid content of 40%, the mixing and stirring speed is 70rpm, and then wet grinding, spray drying, sintering and dry grinding are carried out in sequence to obtain manganese iron phosphate lithium premix, wherein the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.5μm, D100≤1 .5μm, the air inlet temperature during spray drying is 260℃, the exhaust temperature is 100℃, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 150℃ at a heating rate of 3℃ / min, and the temperature is kept for sintering for 1h, and then the temperature is raised to 450℃, and the temperature is kept for sintering for 3h. The dry grinding is carried out using a planetary ball mill. The particle size of the lithium manganese iron phosphate premix after dry grinding is 0.5μm≤D50≤0.6μm, D100≤4μm, and the carbon content is 0.2%; the lithium manganese iron phosphate premix, the second carbon source and water are mixed at a solid content of 40%, and the mixture is The stirring speed is 70rpm, and then spray drying, sintering and crushing are carried out in sequence to obtain lithium manganese iron phosphate material, wherein the inlet air temperature of the spray drying is 260°C, the exhaust air temperature is 100°C, and the sintering process is carried out in a nitrogen atmosphere. The temperature is first raised to 350°C at a heating rate of 3°C / min, and the temperature is kept for 1h, and then the temperature is raised to 700°C, and the temperature is kept for 8h. After sintering, it is crushed to make the particle size of the crushed lithium manganese iron phosphate material 0.8μm≤D50≤1.0μm, D100≤7μm, and the carbon content is 1.3%. The lithium manganese iron phosphate material includes LiFe 0.3 Mn 0.7 Mg 0.001 PO 3.999 F 0.001 and compounding carbon therein.
[0041] (2) Preparation of positive electrode sheet
[0042] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 200 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains lithium iron manganese phosphate electrolyte and ethylenediaminetetraacetic acid as the complex, and the mass ratio of the two is 1000:1.
[0043] Example 2
[0044] (1) Preparation of lithium manganese iron phosphate materials
[0045] The iron source is ferroferric oxide, the manganese source is manganese tetraoxide, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the molar ratio of Fe:Mn:P:F is 0.4:0.6:1:0.003; the lithium source is lithium carbonate, the first carbon source is glucose, and the additive is magnesium oxide, and the molar ratio of P:Li:Mg in the manganese iron phosphate precursor is 1:1.015:0.001; the second carbon source is polyethylene glycol (PEG).
[0046] The iron source, manganese source, phosphorus source, fluorine source and water were mixed at a solid content of 15%, the pH was adjusted to 2.5 with sulfuric acid, and the mixture was mixed evenly at a speed of 300 rpm to obtain a mixed solution A; the mixed solution A was placed in a hydrothermal reactor, reacted for 3 hours at a temperature of 80°C and a stirring speed of 60 rpm, and then centrifuged, filtered, washed and dried with a centrifuge at a speed of 1500 rpm, washed with water 5 times, and dried at 90°C for 6 hours to obtain a solid phase material B; the solid phase material B was placed in a muffle furnace and heated to a temperature of 1500 ℃ / min at a heating rate of 3 ℃ / min. 600°C and sintered for 4h, then crushed to obtain a ferromanganese phosphate precursor, the particle size of the ferromanganese phosphate precursor after crushing is 4μm≤D50≤6μm, D100≤70μm; the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water are mixed at a solid content of 45%, the mixing and stirring speed is 70rpm, and then wet grinding, spray drying, sintering, and dry grinding are carried out in sequence to obtain a manganese iron phosphate lithium premix, wherein the particle size of the slurry after wet grinding is 0.45μm≤D50≤0.55μm, D100 ≤2μm, the air inlet temperature during spray drying is 280℃, the exhaust temperature is 110℃, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 200℃ at a heating rate of 3℃ / min, and the temperature is kept for sintering for 2h, and then the temperature is raised to 450℃, and the temperature is kept for sintering for 4h. The dry grinding is carried out using a planetary ball mill. The particle size of the lithium manganese iron phosphate premix after dry grinding is 0.6μm≤D50≤0.7μm, D100≤5μm, and the carbon content is 0.4%; the lithium manganese iron phosphate premix, the second carbon source and water are mixed at a solid content of 50%, and the mixture is The stirring speed is 100rpm, and then spray drying, sintering and crushing are carried out in sequence to obtain lithium manganese iron phosphate material, wherein the inlet air temperature of the spray drying is 280°C, the exhaust air temperature is 110°C, and the sintering process is carried out in a nitrogen atmosphere. The temperature is first raised to 350°C at a heating rate of 5°C / min, and the temperature is kept for sintering for 1h, and then the temperature is raised to 700°C, and the temperature is kept for sintering for 10h. After sintering, it is crushed to make the particle size of the crushed lithium manganese iron phosphate material 0.8μm≤D50≤1.0μm, D100≤7μm, and the carbon content is 1.3%. The lithium manganese iron phosphate material includes Li 1.015 Fe 0.4 Mn 0.6 Mg 0.001 PO 3.997 F 0.003 and compounding carbon therein.
[0047] (2) Preparation of positive electrode sheet
[0048] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 200 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains lithium iron manganese phosphate electrolyte and the complex is ethylenediaminetetraacetic acid, and the mass ratio of the two is 1000:2.
[0049] Example 3
[0050] (1) Preparation of lithium manganese iron phosphate materials
[0051] The iron source is ferrous oxide, the manganese source is manganese tetraoxide, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the molar ratio of Fe:Mn:P:F is 0.5:0.5:1:0.005; the lithium source is lithium carbonate, the first carbon source is glucose, and the additive is magnesium oxide, and the molar ratio of P:Li:Mg in the manganese iron phosphate precursor is 1:1.03:0.001; the second carbon source is polyethylene glycol (PEG).
[0052] The iron source, manganese source, phosphorus source, fluorine source and water were mixed at a solid content of 20%, the pH was adjusted to 2.3 with sulfuric acid, and the mixture was mixed at a speed of 300rmb to obtain a mixed solution A; the mixed solution A was placed in a hydrothermal reactor, reacted at a temperature of 90°C and a stirring speed of 70rpm for 3h, and then centrifuged, filtered, washed and dried with a centrifuge at a speed of 1500rpm, washed with water 7 times, and dried at 80°C for 5h to obtain a solid phase material B; the solid phase material B was placed in a muffle furnace and heated to a temperature of 5°C / min at a heating rate of 15°C / min. 650°C and sintered for 3h, then crushed to obtain a ferromanganese phosphate precursor, the particle size of the ferromanganese phosphate precursor after crushing is 3μm≤D50≤6μm, D100≤70μm; the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water are mixed at a solid content of 45%, the mixing and stirring speed is 100rpm, and then wet grinding, spray drying, sintering, and dry grinding are carried out in sequence to obtain a manganese iron phosphate lithium premix, wherein the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.55μm, D100≤ 2μm, the inlet air temperature during spray drying is 270℃, the exhaust air temperature is 110℃, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 250℃ at a heating rate of 5℃ / min, and the temperature is kept for sintering for 1.5h, and then the temperature is raised to 450℃, and the temperature is kept for sintering for 3.5h. The dry grinding is carried out using a planetary ball mill. The particle size of the lithium manganese iron phosphate premix after dry grinding is 0.5μm≤D50≤0.7μm, D100≤5μm, and the carbon content is 0.3%; the lithium manganese iron phosphate premix, the second carbon source and water are mixed at a solid content of 45%, The mixing and stirring speed is 80rpm, and then spray drying, sintering and crushing are carried out in sequence to obtain lithium manganese iron phosphate material, wherein the inlet air temperature of the spray drying is 280°C, the exhaust air temperature is 110°C, and the sintering process is carried out in a nitrogen atmosphere. The temperature is first raised to 350°C at a heating rate of 5°C / min, and the temperature is kept for 1h, and then the temperature is raised to 700°C, and the temperature is kept for 9h. After sintering, it is crushed to make the particle size of the crushed lithium manganese iron phosphate material 0.8μm≤D50≤1.0μm, D100≤7μm, and the carbon content is 1.3%. The lithium manganese iron phosphate material includes Li 1.03 Fe 0.5 Mn 0.5 Mg 0.001 PO 3.995 F 0.005 and compounding carbon therein.
[0053] (2) Preparation of positive electrode sheet
[0054] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 150 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains a lithium iron manganese phosphate electrolyte and a complex of sulfosalicylic acid, and the mass ratio of the two is 1000:2.
[0055] Example 4
[0056] (1) Preparation of lithium manganese iron phosphate materials
[0057] The iron source is ferrous oxide, the manganese source is manganese tetraoxide, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the molar ratio of Fe:Mn:P:F is 0.2:0.8:1:0.005; the lithium source is lithium carbonate, the first carbon source is glucose, and the additive is magnesium oxide, and the molar ratio of P:Li:Mg in the manganese iron phosphate precursor is 1:1.03:0.001; the second carbon source is polyethylene glycol (PEG).
[0058] The iron source, manganese source, phosphorus source, fluorine source and water were mixed at a solid content of 20%, the pH was adjusted to 2 with sulfuric acid, and the mixture was mixed evenly at a speed of 400rmb to obtain a mixed solution A; the mixed solution A was placed in a hydrothermal reactor, reacted at a temperature of 90°C and a stirring speed of 70rpm for 3h, and then centrifuged, filtered, washed and dried with a centrifuge at a speed of 1500rpm, washed with water 7 times, and dried at 80°C for 5h to obtain a solid phase material B; the solid phase material B was placed in a muffle furnace and heated to 650°C at a heating rate of 5°C / min; ℃ and sintered for 3h, then crushed to obtain ferromanganese phosphate precursor, the particle size of the ferromanganese phosphate precursor after crushing is 3μm≤D50≤6μm, D100≤70μm; the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water are mixed at a solid content of 45%, the mixing and stirring speed is 100rpm, and then wet grinding, spray drying, sintering and dry grinding are carried out in sequence to obtain manganese iron phosphate lithium premix, wherein the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.55μm, D100≤2μm, During spray drying, the air inlet temperature is 270°C, the exhaust temperature is 110°C, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 250°C at a heating rate of 5°C / min, the temperature is kept for sintering for 1.5 hours, and then the temperature is raised to 450°C, and the temperature is kept for sintering for 3.5 hours. Dry grinding is carried out using a planetary ball mill. The particle size of the lithium manganese iron phosphate premix after dry grinding is 0.5μm≤D50≤0.7μm, D100≤10μm, and the carbon content is 0.3%; the lithium manganese iron phosphate premix, the second carbon source and water are mixed at a solid content of 45%, and the mixture is stirred. The rotation speed is 80rpm, and then spray drying, sintering and crushing are carried out in sequence to obtain lithium manganese iron phosphate material, wherein the inlet air temperature of the spray drying is 280°C, the exhaust air temperature is 110°C, and the sintering process is carried out in a nitrogen atmosphere. The temperature is first raised to 350°C at a heating rate of 5°C / min, and the temperature is kept for 1h, and then the temperature is raised to 700°C, and the temperature is kept for 9h. The crushing is also carried out in a nitrogen atmosphere. The particle size of the crushed lithium manganese iron phosphate material is 0.8μm≤D50≤1.2μm, D100≤10μm, and the carbon content is 1.3%. The lithium manganese iron phosphate material includes Li 1.03 Fe 0.2 Mn 0.8 Mg 0.001 PO 3.995 F 0.005 and compounding carbon therein.
[0059] (2) Preparation of positive electrode sheet
[0060] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 150 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains a lithium iron manganese phosphate electrolyte and a complex of sulfosalicylic acid, and the mass ratio of the two is 1000:2.
[0061] Example 5
[0062] (1) Preparation of lithium manganese iron phosphate materials
[0063] The iron source is ferrous oxide, the manganese source is manganese tetraoxide, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the molar ratio of Fe:Mn:P:F is 0.5:0.5:1:0.005; the lithium source is lithium carbonate, the first carbon source is glucose, and the additive is magnesium oxide, and the molar ratio of P:Li:Mg in the manganese iron phosphate precursor is 1:0.9:0.001; the second carbon source is polyethylene glycol (PEG).
[0064] The iron source, manganese source, phosphorus source, fluorine source and water were mixed at a solid content of 20%, the pH was adjusted to 2.5 with sulfuric acid, and the mixture was mixed evenly at a speed of 300rmb to obtain a mixed solution A; the mixed solution A was placed in a hydrothermal reactor, reacted at a temperature of 90°C and a stirring speed of 70rpm for 3h, and then centrifuged, filtered, washed and dried with a centrifuge at a speed of 1500rpm, washed with water 7 times, and dried at 80°C for 5h to obtain a solid phase material B; the solid phase material B was placed in a muffle furnace and heated to 6 50°C and sintered for 3h, then crushed to obtain a ferromanganese phosphate precursor, the particle size of the ferromanganese phosphate precursor after crushing is 3μm≤D50≤6μm, D100≤70μm; the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water are mixed at a solid content of 45%, the mixing and stirring speed is 70rpm, and then wet grinding, spray drying, sintering, and dry grinding are carried out in sequence to obtain a manganese iron phosphate lithium premix, wherein the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.55μm, D100≤2μ m, the inlet air temperature during spray drying is 270°C, the exhaust air temperature is 110°C, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 250°C at a heating rate of 5°C / min, and the temperature is kept for sintering for 1.5 hours, and then the temperature is raised to 450°C, and the temperature is kept for sintering for 3.5 hours. The dry grinding is carried out using a planetary ball mill. The particle size of the lithium manganese iron phosphate premix after dry grinding is 0.5μm≤D50≤0.7μm, D100≤10μm, and the carbon content is 0.3%; the lithium manganese iron phosphate premix, the second carbon source and water are mixed at a solid content of 45%, and the mixture is stirred for 2 hours. The stirring speed is 80rpm, and then spray drying, sintering and crushing are carried out in sequence to obtain lithium manganese iron phosphate material, wherein the inlet air temperature of the spray drying is 280°C, the exhaust air temperature is 110°C, and the sintering process is carried out in a nitrogen atmosphere. The temperature is first raised to 350°C at a heating rate of 5°C / min, and the temperature is kept for 1h, and then the temperature is raised to 700°C, and the temperature is kept for 9h. After sintering, it is crushed to make the particle size of the crushed lithium manganese iron phosphate material 0.8μm≤D50≤1.2μm, D100≤10μm, and the carbon content is 1.3%. The lithium manganese iron phosphate material includes Li 0.9 Fe 0.5 Mn 0.5 Mg 0.001 PO 3.995 F 0.005 and compounding carbon therein.
[0065] (2) Preparation of positive electrode sheet
[0066] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 150 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains lithium iron manganese phosphate electrolyte and complex sulfosalicylic acid, and the mass ratio of the two is 1000:2.
[0067] Example 6
[0068] (1) Preparation of lithium manganese iron phosphate materials
[0069] The iron source is ferrous oxide, the manganese source is manganese tetraoxide, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the molar ratio of Fe:Mn:P:F is 0.5:0.5:1:0.005; the lithium source is lithium carbonate, the first carbon source is glucose, and the additive is magnesium oxide, and the molar ratio of P:Li:Mg in the manganese iron phosphate precursor is 1:1.03:0.001; the second carbon source is polyethylene glycol (PEG).
[0070] The iron source, manganese source, phosphorus source, fluorine source and water were mixed at a solid content of 20%, the pH was adjusted to 2 with sulfuric acid, and the mixture was mixed evenly at a speed of 300rmb to obtain a mixed solution A; the mixed solution A was placed in a hydrothermal reactor, reacted for 3 hours at a temperature of 90°C and a stirring speed of 70rpm, and then centrifuged, filtered, washed and dried with a centrifuge at a speed of 1500rpm, washed with water 7 times, and dried at 80°C for 5h to obtain a solid phase material B; the solid phase material B was placed in a muffle furnace and heated to 65°C at a heating rate of 5°C / min; 0℃ and sintering for 3h, then crushing to obtain ferromanganese phosphate precursor, the particle size of the ferromanganese phosphate precursor after crushing is 3μm≤D50≤6μm, D100≤70μm; mixing the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water at a solid content of 45%, the mixing and stirring speed is 70rpm, and then wet grinding, spray drying, sintering, and dry grinding are carried out in sequence to obtain manganese iron phosphate lithium premix, wherein the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.55μm, D100≤2μ m, the inlet air temperature during spray drying is 270°C, the exhaust air temperature is 110°C, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 250°C at a heating rate of 5°C / min, and the temperature is kept for 1.5 hours, and then the temperature is raised to 350°C, and the temperature is kept for 2 hours. Dry grinding is carried out using a planetary ball mill. The particle size of the lithium manganese iron phosphate premix after dry grinding is 0.5μm≤D50≤0.7μm, D100≤10μm, and the carbon content is 0.3%; the lithium manganese iron phosphate premix, the second carbon source and water are mixed at a solid content of 45%, and the mixture is The stirring speed is 80rpm, and then spray drying, sintering and crushing are carried out in sequence to obtain lithium manganese iron phosphate material, wherein the inlet air temperature of the spray drying is 280°C, the exhaust air temperature is 110°C, and the sintering process is carried out in a nitrogen atmosphere. The temperature is first raised to 350°C at a heating rate of 5°C / min, and the temperature is kept for 1h, and then the temperature is raised to 850°C, and the temperature is kept for 6h. After sintering, it is crushed to make the particle size of the crushed lithium manganese iron phosphate material 0.8μm≤D50≤1.2μm, D100≤10μm, and the carbon content is 1.3%. The lithium manganese iron phosphate material includes Li 1.03 Fe 0.5 Mn 0.5 Mg 0.001 PO 3.995 F 0.005 and compounding carbon therein.
[0071] (2) Preparation of positive electrode sheet
[0072] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 150 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains lithium iron manganese phosphate electrolyte and complex sulfosalicylic acid, and the mass ratio of the two is 1000:2.
[0073] Example 7
[0074] (1) Preparation of lithium manganese iron phosphate materials
[0075] The iron source is ferrous oxide, the manganese source is manganese oxide, the phosphorus source is ammonium dihydrogen phosphate, the fluorine source is lithium fluoride, and the molar ratio of Fe:Mn:P:F is 0.3:0.7:1:0.001; the lithium source is lithium hydroxide, the first carbon source is sucrose, and the additive is titanium dioxide, and the molar ratio of P:Li:Ti in the manganese iron phosphate precursor is 1:1:0.0008; the second carbon source is polyvinyl alcohol.
[0076] The iron source, manganese source, phosphorus source, fluorine source and water were mixed at a solid content of 25%, the pH was adjusted to 2 with sulfuric acid, and the mixture was mixed at a speed of 350rmb to obtain a mixed solution A; the mixed solution A was placed in a hydrothermal reactor, reacted at a temperature of 100°C and a stirring speed of 70rpm for 3h, and then centrifuged, filtered, washed and dried with a centrifuge at a speed of 1800rpm, washed with water 4 times, and dried at 70°C for 6h to obtain a solid phase material B; the solid phase material B was placed in a muffle furnace and heated to a temperature of 150°C / min at a heating rate of 3°C / min. 500°C and sintered for 4h, then crushed to obtain a ferromanganese phosphate precursor, the particle size of the ferromanganese phosphate precursor after crushing is 3μm≤D50≤4μm, D100≤50μm; the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water are mixed at a solid content of 50%, the mixing and stirring speed is 70rpm, and then wet grinding, spray drying, sintering, and dry grinding are carried out in sequence to obtain a manganese iron phosphate lithium premix, wherein the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.55μm, D100≤ 2μm, the inlet air temperature during spray drying is 260°C, the exhaust air temperature is 100°C, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 150°C at a heating rate of 3°C / min, the temperature is kept for sintering for 1h, and then the temperature is raised to 450°C, and the temperature is kept for sintering for 4h. The dry grinding is carried out using a planetary ball mill. The particle size of the lithium manganese iron phosphate premix after dry grinding is 0.5μm≤D50≤0.6μm, D100≤4μm, and the carbon content is 0.4%; the lithium manganese iron phosphate premix, the second carbon source and water are mixed at a solid content of 40%, and the mixture is stirred. The stirring speed is 70rpm, and then spray drying, sintering and crushing are carried out in sequence to obtain lithium manganese iron phosphate material, wherein the inlet air temperature of the spray drying is 260°C, the exhaust air temperature is 100°C, and the sintering process is carried out in a nitrogen atmosphere. The temperature is first raised to 350°C at a heating rate of 3°C / min, and the temperature is kept for 2 hours, and then the temperature is raised to 700°C, and the temperature is kept for 10 hours. After sintering, it is crushed to make the particle size of the crushed lithium manganese iron phosphate material 0.8μm≤D50≤1.2μm, D100≤10μm, and the carbon content is 1.5%. The lithium manganese iron phosphate material includes LiFe 0.3 Mn 0.7 Ti 0.0008 PO 3.999 F 0.001 and compounding carbon therein.
[0077] (2) Preparation of positive electrode sheet
[0078] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 30%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 200 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains lithium iron manganese phosphate electrolyte and ethylenediaminetetraacetic acid as the complex, and the mass ratio of the two is 1000:1.
[0079] Example 8
[0080] (1) Preparation of lithium manganese iron phosphate materials
[0081] The iron source is ferric sulfate, the manganese source is manganese sulfate, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the molar ratio of Fe:Mn:P:F is 0.3:0.7:1:0.001; the lithium source is lithium oxide, the first carbon source is citric acid, and the additive is aluminum oxide, and the molar ratio of P:Li:Al in the manganese iron phosphate precursor is 1:1:0.0012; the second carbon source is polyacrylonitrile.
[0082] The iron source, manganese source, phosphorus source, fluorine source and water were mixed at a solid content of 10%, the pH was adjusted to 2 with sulfuric acid, and the mixture was mixed evenly at a speed of 350rmb to obtain a mixed solution A; the mixed solution A was placed in a hydrothermal reactor, reacted for 5 hours at a temperature of 80°C and a stirring speed of 70rpm, and then centrifuged, filtered, washed and dried with a centrifuge at a speed of 1500rpm, washed with water 7 times, and dried at 90°C for 4h to obtain a solid phase material B; the solid phase material B was placed in a muffle furnace and heated to 6 at a heating rate of 5°C / min 50°C and sintered for 3h, then crushed to obtain a ferromanganese phosphate precursor, the particle size of the ferromanganese phosphate precursor after crushing is 3μm≤D50≤6μm, D100≤70μm; the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water are mixed at a solid content of 40%, the mixing and stirring speed is 70rpm, and then wet grinding, spray drying, sintering, and dry grinding are carried out in sequence to obtain a manganese iron phosphate lithium premix, wherein the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.55μm, D100≤ 2μm, the air inlet temperature during spray drying is 280°C, the exhaust temperature is 110°C, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 250°C at a heating rate of 5°C / min, and the temperature is kept for 2h, and then the temperature is raised to 550°C, and the temperature is kept for 3h. The dry grinding is carried out using a planetary ball mill. The particle size of the lithium manganese iron phosphate premix after dry grinding is 0.5μm≤D50≤0.7μm, D100≤5μm, and the carbon content is 0.2%; the lithium manganese iron phosphate premix, the second carbon source and water are mixed at a solid content of 50%, and the mixture is mixed. The stirring speed is 70rpm, and then spray drying, sintering and crushing are carried out in sequence to obtain lithium manganese iron phosphate material, wherein the inlet air temperature of the spray drying is 280°C, the exhaust air temperature is 110°C, and the sintering process is carried out in a nitrogen atmosphere. The temperature is first raised to 450°C at a heating rate of 5°C / min, and the temperature is kept for 1h, and then the temperature is raised to 780°C, and the temperature is kept for 8h. After sintering, it is crushed to make the particle size of the crushed lithium manganese iron phosphate material 0.8μm≤D50≤1.2μm, D100≤10μm, and the carbon content is 1.4%. The lithium manganese iron phosphate material includes LiFe 0.3 Mn 0.7 Al 0.0012 PO 3.999 F 0.001 and compounding carbon therein.
[0083] (2) Preparation of positive electrode sheet
[0084] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 30%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 200 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains lithium iron manganese phosphate electrolyte and the complex is sulfosalicylic acid, and the mass ratio of the two is 1000:2.
[0085] Example 9
[0086] (1) Preparation of lithium manganese iron phosphate materials
[0087] The iron source is ferric oxide, the manganese source is manganese tetraoxide, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the molar ratio of Fe:Mn:P:F is 0.3:0.7:1:0.001; the lithium source is lithium carbonate, the first carbon source is glucose, the additive is niobium pentoxide, and the molar ratio of P:Li:Nb in the manganese iron phosphate precursor is 1:1:0.001; the second carbon source is polyethylene glycol (PEG).
[0088] The iron source, manganese source, phosphorus source, fluorine source and water were mixed at a solid content of 10%, the pH was adjusted to 2 with sulfuric acid, and the mixture was mixed evenly at a speed of 300rmb to obtain a mixed solution A; the mixed solution A was placed in a hydrothermal reactor, reacted at a temperature of 70°C and a stirring speed of 50rpm for 3h, and then centrifuged, filtered, washed with water, and dried with a centrifuge at a speed of 1500rpm, washed with water 4 times, and dried at 70°C for 6h to obtain a solid phase material B; the solid phase material B was placed in a muffle furnace and heated to 5 at a heating rate of 3°C / min; 00℃ and sintering for 3h, then crushing to obtain ferromanganese phosphate precursor, the particle size of the ferromanganese phosphate precursor after crushing is 3μm≤D50≤4μm, D100≤50μm; mixing the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water at a solid content of 40%, the mixing and stirring speed is 70rpm, and then wet grinding, spray drying, sintering and dry grinding are carried out in sequence to obtain manganese iron phosphate lithium premix, wherein the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.5μm, D100≤1 .5μm, the air inlet temperature during spray drying is 260℃, the exhaust temperature is 100℃, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 150℃ at a heating rate of 3℃ / min, and the temperature is kept for sintering for 1h, and then the temperature is raised to 450℃, and the temperature is kept for sintering for 3h. The dry grinding is carried out using a planetary ball mill. The particle size of the lithium manganese iron phosphate premix after dry grinding is 0.5μm≤D50≤0.6μm, D100≤4μm, and the carbon content is 0.2%; the lithium manganese iron phosphate premix, the second carbon source and water are mixed at a solid content of 40%, and the mixture is The stirring speed is 70rpm, and then spray drying, sintering and crushing are carried out in sequence to obtain lithium manganese iron phosphate material, wherein the inlet air temperature of the spray drying is 260°C, the exhaust air temperature is 100°C, and the sintering process is carried out in a nitrogen atmosphere. The temperature is first raised to 350°C at a heating rate of 3°C / min, and the temperature is kept for 1h, and then the temperature is raised to 700°C, and the temperature is kept for 8h. After sintering, it is crushed to make the particle size of the crushed lithium manganese iron phosphate material 0.8μm≤D50≤1.0μm, D100≤7μm, and the carbon content is 1.3%. The lithium manganese iron phosphate material includes LiFe 0.3 Mn 0.7 Nb 0.001 PO 3.999 F 0.001 and compounding carbon therein.
[0089] (2) Preparation of positive electrode sheet
[0090] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 200 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains lithium iron manganese phosphate electrolyte and ethylenediaminetetraacetic acid as the complex, and the mass ratio of the two is 1000:1.
[0091] Example 10
[0092] (1) Preparation of lithium manganese iron phosphate materials
[0093] The iron source is ferroferric oxide, the manganese source is manganese tetraoxide, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the molar ratio of Fe:Mn:P:F is 0.3:0.7:1:0.001; the lithium source is lithium carbonate, the first carbon source is glucose, the additive is yttrium trioxide, and the molar ratio of P:Li:Y in the manganese iron phosphate precursor is 1:1:0.001; the second carbon source is polyethylene glycol (PEG).
[0094] The iron source, manganese source, phosphorus source, fluorine source and water were mixed at a solid content of 10%, the pH was adjusted to 2 with sulfuric acid, and the mixture was mixed evenly at a speed of 300rmb to obtain a mixed solution A; the mixed solution A was placed in a hydrothermal reactor, reacted at a temperature of 70°C and a stirring speed of 50rpm for 3h, and then centrifuged, filtered, washed with water, and dried with a centrifuge at a speed of 1500rpm, washed with water 4 times, and dried at 70°C for 6h to obtain a solid phase material B; the solid phase material B was placed in a muffle furnace and heated to 5 at a heating rate of 3°C / min; 00℃ and sintering for 3h, then crushing to obtain ferromanganese phosphate precursor, the particle size of the ferromanganese phosphate precursor after crushing is 3μm≤D50≤4μm, D100≤50μm; mixing the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water at a solid content of 40%, the mixing and stirring speed is 70rpm, and then wet grinding, spray drying, sintering and dry grinding are carried out in sequence to obtain manganese iron phosphate lithium premix, wherein the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.5μm, D100≤1 .5μm, the air inlet temperature during spray drying is 260℃, the exhaust temperature is 100℃, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 150℃ at a heating rate of 3℃ / min, and the temperature is kept for sintering for 1h, and then the temperature is raised to 450℃, and the temperature is kept for sintering for 3h. The dry grinding is carried out using a planetary ball mill. The particle size of the lithium manganese iron phosphate premix after dry grinding is 0.5μm≤D50≤0.6μm, D100≤4μm, and the carbon content is 0.2%; the lithium manganese iron phosphate premix, the second carbon source and water are mixed at a solid content of 40%, and the mixture is The stirring speed is 70rpm, and then spray drying, sintering and crushing are carried out in sequence to obtain lithium manganese iron phosphate material, wherein the inlet air temperature of the spray drying is 260°C, the exhaust air temperature is 100°C, and the sintering process is carried out in a nitrogen atmosphere. The temperature is first raised to 350°C at a heating rate of 3°C / min, and the temperature is kept for 1h, and then the temperature is raised to 700°C, and the temperature is kept for 8h. After sintering, it is crushed to make the particle size of the crushed lithium manganese iron phosphate material 0.8μm≤D50≤1.0μm, D100≤7μm, and the carbon content is 1.3%. The lithium manganese iron phosphate material includes LiFe 0.3 Mn 0.7 Y 0.001 PO 3.999 F 0.001 and compounding carbon therein.
[0095] (2) Preparation of positive electrode sheet
[0096] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 200 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains lithium iron manganese phosphate electrolyte and ethylenediaminetetraacetic acid as the complex, and the mass ratio of the two is 1000:1.
[0097] Embodiment 11
[0098] (1) Preparation of positive electrode sheet
[0099] The lithium iron manganese phosphate material prepared in Example 1, conductive carbon black and polyvinylidene fluoride are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain a lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 200 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains a lithium iron manganese phosphate electrolyte and a complex of ethylenediaminetetraacetic acid, and the mass ratio of the two is 1000:0.5.
[0100] Comparative Example 1
[0101] The iron source is ferrous oxide, the manganese source is trimanganese tetraoxide, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the lithium source is lithium carbonate. The iron source, the manganese source, the phosphorus source, the fluorine source, glucose, magnesium oxide and water are mixed at a solid content of 40%, wherein the molar ratio of Fe:Mn:P:Li:F is 0.3:0.7:1:1:0.001, and the magnesium oxide and the phosphorus source have a P:Mg ratio of 1:0.001. The mixture is mixed and stirred at a rotation speed of 70 rpm, and then wet-grinded, spray-dried, sintered and crushed in sequence to obtain lithium manganese iron phosphate. The wet-grinded The particle size of the slurry after grinding is 0.4μm≤D50≤0.5μm, D100≤1.5μm, the air inlet temperature during spray drying is 260℃, the exhaust temperature is 100℃, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 350℃ at a heating rate of 3℃ / min, and the temperature is kept for 1h, and then the temperature is raised to 700℃, and the temperature is kept for 8h. After sintering, it is crushed to make the particle size of the crushed lithium manganese iron phosphate material 0.8μm≤D50≤1.0μm, D100≤7μm, and the carbon content is 1.3%. The lithium manganese iron phosphate material includes LiFe 0.3 Mn 0.7 Mg 0.001 PO 3.999 F 0.001 and compounding carbon therein.
[0102] (2) Preparation of positive electrode sheet
[0103] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 200 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains lithium iron manganese phosphate electrolyte and ethylenediaminetetraacetic acid as the complex, and the mass ratio of the two is 1000:1.
[0104] Comparative Example 2
[0105] (1) Preparation of lithium manganese iron phosphate materials
[0106] The iron source is ferrous oxide, the manganese source is manganese tetraoxide, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the molar ratio of Fe:Mn:P:F is 0.3:0.7:1:0.001; the lithium source is lithium carbonate, the first carbon source is glucose, and the additive is magnesium oxide, and the molar ratio of P:Li:Mg in the manganese iron phosphate precursor is 1:1:0.001.
[0107] The iron source, manganese source, phosphorus source, fluorine source and water are mixed at a solid content of 10%, the pH is adjusted to 2.5 with sulfuric acid, and mixed evenly at a speed of 350rmb to obtain a mixed solution A; the mixed solution A is placed in a hydrothermal reactor, reacted at a temperature of 70°C and a stirring speed of 50rpm for 3h, and then centrifuged, filtered, washed and dried with a centrifuge, the centrifuge speed is 1500rpm, washed with water 4 times, and dried at 70°C for 6h to obtain a solid phase material B; the solid phase material B is placed in a muffle furnace and heated to 500°C at a heating rate of 3°C / min and sintered for 3h, and then crushed to obtain a ferromanganese phosphate precursor, and the particle size of the ferromanganese phosphate precursor after crushing is 3μm≤D50 ≤4μm, D100≤50μm; mix the ferromanganese phosphate precursor, lithium source, first carbon source, additive and water at a solid content of 40%, mix at a mixing speed of 70rpm, and then sequentially carry out wet grinding, spray drying, sintering and dry grinding to obtain the lithium ferromanganese phosphate material, wherein the inlet air temperature of the spray drying is 260°C, the exhaust air temperature is 100°C, the sintering process is carried out in a nitrogen atmosphere, and the temperature is first raised to 350°C at a heating rate of 3°C / min, and the temperature is kept for 1h, and then the temperature is raised to 700°C, and the temperature is kept for 8h. After sintering, it is crushed to make the particle size of the crushed lithium ferromanganese phosphate material 0.8μm≤D50≤1.0μm, D100≤7μm, and the carbon content is 1.3%. The lithium ferromanganese phosphate material includes LiFe 0.3 Mn 0.7 Mg 0.001 PO 3.999 F0.001 and compounding carbon therein.
[0108] (2) Preparation of positive electrode sheet
[0109] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 200 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains lithium iron manganese phosphate electrolyte and ethylenediaminetetraacetic acid as the complex, and the mass ratio of the two is 1000:1.
[0110] Comparative Example 3
[0111] (1) Preparation of lithium manganese iron phosphate materials
[0112] The iron source is ferrous oxide, the manganese source is manganese tetraoxide, the phosphorus source is phosphoric acid, the fluorine source is hydrofluoric acid, and the molar ratio of Fe:Mn:P:F is 0.3:0.7:1:0.001; the lithium source is lithium carbonate, the first carbon source is glucose, and the molar ratio of P:Li in the manganese iron phosphate precursor is 1:1; the second carbon source is polyethylene glycol (PEG).
[0113] The iron source, manganese source, phosphorus source, fluorine source and water were mixed at a solid content of 10%, the pH was adjusted to 2.5 with sulfuric acid, and the mixture was mixed evenly at a speed of 350rmb to obtain a mixed solution A; the mixed solution A was placed in a hydrothermal reactor, reacted for 3 hours at a temperature of 70°C and a stirring speed of 50rpm, and then centrifuged, filtered, washed and dried with a centrifuge at a speed of 1500rpm, washed with water 4 times, and dried at 70°C for 6h to obtain a solid phase material B; the solid phase material B was placed in a muffle furnace and heated at a heating rate of 3°C / min. The mixture is heated to 500°C and sintered for 3 hours, and then crushed to obtain a ferromanganese phosphate precursor, wherein the particle size of the ferromanganese phosphate precursor after crushing is 3μm≤D50≤4μm, and D100≤50μm; the ferromanganese phosphate precursor, the lithium source, the first carbon source and water are mixed at a solid content of 40%, and the mixing and stirring speed is 70rpm, and then wet grinding, spray drying, sintering and dry grinding are carried out in sequence to obtain a manganese iron phosphate lithium premix, wherein the particle size of the slurry after wet grinding is 0.4μm≤D50≤0.5μm, and D100≤1. 5μm, the inlet air temperature during spray drying is 260°C, the exhaust air temperature is 100°C, the sintering process is carried out in a nitrogen atmosphere, the temperature is first raised to 150°C at a heating rate of 3°C / min, the temperature is kept for sintering for 1h, and then the temperature is raised to 450°C, and the temperature is kept for sintering for 3h. The dry grinding is carried out using a planetary ball mill. The particle size of the lithium manganese iron phosphate premix after dry grinding is 0.5μm≤D50≤0.6μm, D100≤4μm, and the carbon content is 0.2%; the lithium manganese iron phosphate premix, the second carbon source and water are mixed at a solid content of 40%, and the mixture is The stirring speed is 70rpm, and then spray drying, sintering and crushing are carried out in sequence to obtain lithium manganese iron phosphate material, wherein the inlet air temperature of the spray drying is 260°C, the exhaust air temperature is 100°C, and the sintering process is carried out in a nitrogen atmosphere. The temperature is first raised to 350°C at a heating rate of 3°C / min, and the temperature is kept for 1h, and then the temperature is raised to 700°C, and the temperature is kept for 8h. After sintering, it is crushed to make the particle size of the crushed lithium manganese iron phosphate material 0.8μm≤D50≤1.0μm, D100≤7μm, and the carbon content is 1.3%. The lithium manganese iron phosphate material includes LiFe 0.3 Mn 0.7 PO 4 F 0.001 and compounding carbon therein.
[0114] (2) Preparation of positive electrode sheet
[0115] The lithium iron manganese phosphate material, conductive carbon black and polyvinylidene fluoride obtained above are mixed with N-methylpyrrolidone in a slurry mixer at a mass ratio of 0.95:0.03:0.02 to obtain lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 200 μm, and then the positive electrode of the battery is prepared through rolling, assembly and injection processes. The injection contains lithium iron manganese phosphate electrolyte and ethylenediaminetetraacetic acid as the complex, and the mass ratio of the two is 1000:1.
[0116] Comparative Example 4
[0117] (1) Preparation of positive electrode sheet
[0118] The lithium iron manganese phosphate material prepared in Example 1, conductive carbon black and polyvinylidene fluoride are mixed in a slurry mixer at a mass ratio of 0.95:0.03:0.02 with N-methylpyrrolidone to obtain a lithium iron manganese phosphate slurry, wherein the solid content of the mixed slurry is 40%; the lithium iron manganese phosphate slurry is coated on a carbon-coated aluminum foil current collector with a coating thickness of 200 μm, and then the battery positive electrode is prepared through rolling, assembly and liquid injection processes.
[0119] The positive electrode sheet and the negative electrode sheet prepared in each embodiment are used to prepare a lithium-ion battery, and then the performance thereof is tested. The preparation of the negative electrode sheet and the preparation of the lithium-ion battery are carried out according to the following method:
[0120] (1) Preparation of negative electrode sheet:
[0121] Potassium chloride, dimethyl carbonate, conductive carbon black and water were taken in a mass ratio of 0.95:0.03:0.02:0.8, mixed in a slurry mixer and stirred at 1000 rpm for 12 hours to obtain a negative electrode mixed slurry. The negative electrode mixed slurry was coated on an 8 μm copper foil and dried at 100°C for 3 hours. After drying, an unrolled negative electrode sheet with a coating thickness of 70 μm was obtained, and a negative electrode sheet was obtained after rolling.
[0122] (2) Preparation of lithium-ion batteries:
[0123] The above-mentioned positive electrode plate, negative electrode plate and PP separator Celgard 2400 with a thickness of 15 to 25 μm are stacked to obtain a bare battery cell. After the battery cell is placed in an aluminum-plastic film, a lithium hexafluorophosphate (LiPF6) solution with a concentration of 1 mol / L is injected. The solvent is an electrolyte of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate with a volume ratio of 1:1:1. After a packaging process, a lithium-ion battery is obtained.
[0124] (3) Performance testing methods
[0125] Material compaction density (g / cc): Weigh 0.5g of lithium manganese iron phosphate material, put it into the tablet press mold, place it in the tablet press, apply 5MPa pressure, hold the pressure for 30 seconds, and demold to test the material compaction density performance;
[0126] Powder resistivity (Ω·cm): Weigh 0.5g of lithium manganese iron phosphate material, place it in the mold of the powder resistivity testing machine, apply a pressure of 100MPa, hold the pressure for 30 seconds, and test the resistivity of the powder material;
[0127] Temperature rise (℃): During 1C charging, the temperature of the battery before and after charging is tested using the temperature sensing line of the test equipment. The difference between the two is the temperature rise.
[0128] First efficiency (%): first charge gram capacity / first discharge gram capacity; wherein, 0.05C is charged for 3h, 0.1C is charged until the voltage reaches 4.25V, and the current is less than 0.05C; after the first charge is completed, the first charge capacity (mAh) is obtained, and the charge capacity / mass of lithium manganese iron phosphate in the electrode is obtained to obtain the first charge gram capacity (mAh / g); after the first charge is completed, 0.1C is discharged, and the first discharge is completed at a cut-off voltage of 2V, and the discharge capacity / mass of active material is obtained to obtain the first discharge gram capacity (mAh / g);
[0129] 1C discharge capacity (mAh / g): 1C discharge drops to a voltage of 2.5V, and the discharge capacity is obtained. The 1C capacity is the discharge capacity / mass of lithium manganese iron phosphate in the electrode, and the 1C capacity is obtained.
[0130] 1C500 cycles / %: capacity retention rate after charge and discharge at 1C current density at 25°C; 500-cycle 1C discharge capacity / 1C first charge capacity.
[0131] Table 1
[0132]
[0133]
[0134] As can be seen from Table 1, in Example 1 and Implementation 3, as well as Example 7 and Example 10 of the present invention, when preparing lithium manganese iron phosphate materials, the addition amount of various elements and the preparation conditions are controlled within the preferred range of the present invention, and the obtained lithium manganese iron phosphate materials have better compaction density performance and smaller resistivity. When the above materials are applied to batteries, their 1C discharge capacity, 1C500 cycle and first effect all have better effects. However, in Examples 4 to 6, when preparing lithium manganese iron phosphate materials, the addition amount of some elements is outside the range described in the present invention, and the material effect and battery performance are worse. In Example 11, when preparing the positive electrode of the battery, the addition amount of the complexing agent is not within the preferred range of the present invention, and the battery performance is also worse than that of Example 1 and Implementation 3, as well as Example 7 and Example 10 of the present invention.
[0135] Among Comparative Examples 1 to 3, Comparative Example 1 adopts a conventional method for preparing lithium manganese iron phosphate material. Although the material components are the same as those in Example 1, the overall effect when it is used in the battery is very different; Comparative Example 2 is only carbon coated once, even if the carbon content in the material is similar to that in Example 1, the effect is very different; Comparative Example 3 does not perform metal doping, and the use effect is also much worse. Comparative Example 4 does not add a complexing agent when preparing the positive electrode plate of the battery, and the overall performance of the battery is also much worse.
[0136] From the above analysis, it can be seen that by using the method for preparing lithium iron manganese phosphate material provided by the present invention and controlling the preparation conditions within the preferred range, the obtained lithium iron manganese phosphate material can have better compaction performance and smaller resistivity, and the prepared lithium iron manganese phosphate material is then prepared into a battery using the method of the present invention. The battery has better cycle stability and capacity, and the comprehensive performance of the obtained battery can be further improved.
[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing lithium manganese iron phosphate material, characterized in that: The preparation method comprises the following steps: Step (1), mixing an iron source, a manganese source, a phosphorus source, a fluorine source and water, and then adjusting the pH with sulfuric acid to obtain a mixed solution A; Step (2), heating the mixed solution A to react; performing solid-liquid separation, sintering and crushing on the mixed slurry obtained by the reaction to obtain a ferromanganese phosphate precursor; Step (3), mixing the ferromanganese phosphate precursor, the lithium source, the first carbon source, the additive and water, and then sequentially performing wet grinding, first spray drying, first sintering and dry grinding to obtain a manganese phosphate lithium premix; Step (4), mixing the lithium manganese iron phosphate premix, the second carbon source and water, and then sequentially performing a second spray drying, a second sintering and a pulverizing to obtain the lithium manganese iron phosphate material.
2. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The molar ratio of Fe:Mn:P:F in the iron source, the manganese source, the phosphorus source and the fluorine source in the step (1) is X:(1-X):1:Y, wherein X is 0.3 to 0.5 and Y is 0.001 to 0.
005.
3. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The molar ratio of P:Li:M in the ferromanganese phosphate precursor, the lithium source and the additive in step (3) is 1:(1-1.03): (0.0008~0.0012), where M is the metal element in the additive.
4. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The first carbon source is one or more of glucose, sucrose and citric acid; the second carbon source is one or more of polyethylene glycol, polyvinyl alcohol and polyacrylonitrile; Preferably, the additive is one or more of magnesium oxide, titanium dioxide, aluminum oxide, niobium pentoxide and yttrium oxide.
5. The method for preparing the lithium iron manganese phosphate material according to any one of claims 1 to 3, characterized in that: In the step (1), the pH is adjusted to 2-2.5 with sulfuric acid, and preferably the solid content of the mixed solution A is 10-25%; Preferably, the iron source is one or more of ferrous oxide, ferrous oxide, ferrosoferric oxide and ferric sulfate; Preferably, the manganese source is one or more of manganese oxide, manganese tetraoxide and manganese sulfate; Preferably, the phosphorus source is phosphoric acid and / or diammonium phosphate; Preferably, the fluorine source is lithium fluoride and / or hydrofluoric acid; Preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide and lithium oxide.
6. The method for preparing the lithium iron manganese phosphate material according to any one of claims 1 to 3, characterized in that: The heating reaction time in step (2) is 3 to 5 hours, the temperature is 80 to 100° C., and the stirring speed is 50 to 70 rpm; Preferably, during the solid-liquid separation operation in step (2), the mixed slurry is centrifuged, filtered, washed with water, and dried; Further preferably, the centrifugal speed is 1500-1800 rpm, the water washing times are 4-7 times, the drying temperature is 70-90°C, and the drying time is 4-6 hours; Preferably, the sintering process in step (2) is heated to 500-650° C. at a heating rate of 3-5° C. / min, and sintered at this temperature for 3-4 hours; Preferably, the particle size of the ferromanganese phosphate precursor obtained after the crushing in the step (2) is 3 μm≤D50≤6 μm, D100≤70 μm; Preferably, the first sintering and the second sintering are performed in a nitrogen or inert gas atmosphere, and preferably the inert gas is argon.
7. The method for preparing the lithium iron manganese phosphate material according to any one of claims 1 to 3, characterized in that: The solid content of the mixed slurry in step (3) is 40-50%; Preferably, the particle size of the slurry after wet grinding is 0.4 μm ≤ D50 ≤ 0.55 μm, D100 ≤ 2 μm; Preferably, the inlet air temperature of the first spray drying is 260-280°C, and the exhaust air temperature is 100-110°C; Preferably, in the first sintering process, the temperature is first increased to 150-250°C at a heating rate of 3-5°C / min, and the temperature is kept at 1-2 hours, and then the temperature is increased to 450-550°C, and the temperature is kept at 3-4 hours; Preferably, the particle size of the lithium iron manganese phosphate premix obtained after the dry grinding is 0.5 μm≤D50≤0.7 μm, D100≤5 μm; Preferably, the carbon content of the lithium manganese iron phosphate premix is 0.2-0.4%.
8. The method for preparing the lithium iron manganese phosphate material according to any one of claims 1 to 3, characterized in that: The solid content of the mixed slurry in step (4) is 40-50%; Preferably, the inlet air temperature of the second spray drying is 260-280°C, and the exhaust air temperature is 100-110°C; Preferably, the second sintering process is firstly heated to 350-450°C at a heating rate of 3-5°C / min, sintered at this temperature for 1-2 hours, and then heated to 700-780°C, sintered at this temperature for 8-10 hours; Preferably, the particle size of the lithium manganese iron phosphate material obtained after the pulverization is 0.8 μm≤D50≤1.2 μm, D100≤10μm; Preferably, the carbon content of the lithium manganese iron phosphate material is 1.3-1.5%.
9. A lithium manganese iron phosphate material, characterized in that: The method for preparing the lithium iron manganese phosphate material according to any one of claims 1 to 8, wherein the lithium iron manganese phosphate material comprises Li (1~1.03) Fe X Mn (1-X) M (0.0008~0.0012) PO (4-Y) F Y and carbon compounded therein, wherein X is 0.3-0.5, Y is 0.001-0.005, the carbon content is 1.3-1.5%, and M is one or more metal elements selected from magnesium oxide, titanium dioxide, aluminum oxide, niobium pentoxide and yttrium oxide.
10. A positive electrode plate for a battery, characterized in that: Containing the lithium manganese iron phosphate material as described in claim 9; preferably, the method for preparing the positive electrode sheet of the battery comprises the following steps: S1: mixing the lithium iron manganese phosphate material with a conductive agent and a binder to obtain a lithium iron manganese phosphate slurry; S2: coating the lithium manganese iron phosphate slurry on a carbon-coated aluminum foil current collector, and then rolling, assembling, and injecting liquid to form a battery positive electrode; Preferably, the solid content of the lithium manganese iron phosphate slurry is 30-40%; Preferably, the conductive agent is conductive carbon black, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone; Preferably, the injection solution contains a lithium iron manganese phosphate electrolyte and a complex, and the mass ratio of the lithium iron manganese phosphate electrolyte to the complex in the injection solution is 1000:(1-2); Preferably, the complex is ethylenediaminetetraacetic acid and / or sulfosalicylic acid; Preferably, the coating thickness is 150-200 μm.
Citation Information
Patent Citations
Fluorinion-doped lithium iron phosphate material and preparation methods thereof
CN102024951A
Fluorine-doped lithium ferric manganese phosphate cathode material and preparation method thereof
CN105470468A
Fluorine-doped carbon-coated positive electrode composite material and preparation method and application thereof
CN105895879A
Doped lithium iron phosphate cathode material and preparation method of same
CN107887583A
Preparation method of fluorine-doped lithium-rich manganese-based positive electrode material
CN112701273A
Cited By
Lithium ferric manganese phosphate composite positive electrode material as well as preparation method and application thereof
CN120690957A
Ultralow-viscosity lithium manganese iron phosphate material and preparation method thereof
CN121536900A
An ultralow viscosity lithium manganese iron phosphate material and a preparation method thereof
CN121536900B